Analysis of Travel Agent Online Marketing Strategies on Social Media Content Using Sentiment Analysis and Social Network Analysis - Isya', Ana Diyanti Khoirul; Suratno, Bambang; Azzam, Abdullah (Universitas Bina Darma, 2023)
The growth and development of the internet users have given Indonesia an opportunity to develop internet-based services, such as online travel agents (OTA). Along with this OTA development, conventional travel agents were declining. Many conventional travel agents have decided to switch to online travel agents. The emergence of new OTAs has also made OTAs competition more challenging. Thus, a lesson learned from the market leader OTA is expected to help new OTAs surviving the competition. This research uses the sentiment analysis method to understand consumers' perceptions towards OTA and uses the social network analysis method to recognize actors who play significant roles in the travel agent business network. Lastly, the marketing strategies of the major and well-known OTAs perceived by online consumers was analyzed. Using the data collected from three major OTAs social media network (i.e., Traveloka, Tiket, and Booking), it was found that the general impression of consumers towards OTA is a positive sentiment. Furthermore, each key actor for each OTAs can be recognized. Lastly, marketing strategies can be proposed, namely by providing the complete product offerings, provide competitive price, creating special promos for consumers, promotion to be carried out on all social media using Bahasa Indonesia, and make the products offered available throughout Indonesia and can be used by everyone, especially travelers.